Electromyographic Findings of Spinal Accessory Nerve Functions after Neck Dissections - Aslı Batur Çalış; Hüseyin Seven; Suat Turgut; Münevver Çelik; Yunus Diler (Turkish Archives of Otorhinolaryngology, 2002)

(untitled)
In our study, we aimed to investigate spinal accessory nerve (SAN) functions after neck dissections (ND), the effect of postoperative radiotherapy (RT) on postoperative SAN dysfunction and the effect of systemic peripheral neuropathy (SPN) on electromyographic (EMG) findings of SAN dysfunction. Twenty patients who had undergone ND (35, in total) in our clinic between December 1993 and September 1998 were studied retrospectively using postoperative subjective and objective clinical examination and EMG. All patients answered a questionnaire regarding postoperative discomfort, pain, limitation of shoulder movements and loss of daily activities. Anatomical changes, degree of active abduction of the upper extremity and muscle power were examined. After routine neurological examination and routine EMG searching for any SPN, the SAN and the trapezius muscle were examined with the EMG and results were classified as normal or slight/intermediate/serious dysfunction. Three cases with the SAN sacrified showed intermediate or serious dysfunction in the EMG. Out of 32 cases with the SAN preserved, 22 (70%) showed normal findings or slight dysfunction in the EMG. In both groups, SAN dysfunction did not cause significant clinical findings and was not the primary cause of loss of daily activities. Out of 10 cases with intermediate-serious dysfunction in EMG, 5 also had findings of SPN observed during routine EMG examination. In all these cases, EMG results were not correlated to clinical symptoms and findings. So one might suggest, that the presence of SPN may cause difficulties in interpreting the EMG findings of SAN dysfunction, if it is overlooked. Postoperative RT was observed to increase the degree of SAN dysfunction, whether it is preserved or not.